A brief agricultural history of cannabis in Africa, from prehistory to canna-colony - Chris S. Duvall (EchoGéo)
This article outlines four historical phases of cannabis cultivation in Africa. First, during the plant’s initial dispersal across the continent, people developed diverse cultures of cannabis farming and use. Second, several formal markets for cannabis developed under colonial regimes, although colonialists more widely suppressed the crop. Third, twentieth-century drug laws changed the economics of production, causing cannabis farming to become particularly attractive to resource-poor farmers. Finally, several countries have recently legalized cannabis cultivation in specific contexts. Altogether, the crop’s agricultural history has produced relationships that enable Global Northerners to extract more value from African resources than African farmers can extract.